Sharing energy resources of Eastern Mediterranean: Regional and global dynamics - Nesrin Demir; Osman Tekir (Economic and Environmental Studies (E&ES), 2017)
The newly discovered gas sources establish a political and economic ground for the formation of regional and global alliances in the Eastern Mediterranean. Although these new discoveries have the potential to alter the functioning of po litics and the economy, current and past controversies, political instability, how natural gas will be shared between countries, and competition power of countries in natural gas market prevent natural gas production and exploration at the Eastern Mediterr anean bay. On the other hand, in consequence of gas explorations that in the last decade, it is expected that in the near future there will be much more regional and global playmakers in the Eastern Mediterranean. Research, development and export speed of the gas reservoirs, each and every decision to be taken by the countries in the Eastern Mediterranean, will be the dynamic weighted decisions of the national energy politics and regional politics. That's why, in this study, the lead energy players in the E astern Mediterranean and their disagreements are investigated and, the goals and targets of the global powers on the energy resources available in the Eastern Mediterranean are analysed.
Keywords: Q34; F59; Q48; 330; Energy; natural gas; shale gas; Eastern Mediterranean